Global migration pact and its impact in Peru - Leyva Carbonel, Jaddi N. (2019)
The present work has the objective of analyze and understand the migration processes that happens at a global level. This we elaborate with a study of the intentions of organization like the ONU for the execution of programs which can develop an adequate migratory process. In the study, we can see that there are many countries that are in favor and against if it affects  the sovereignty.